Has rural collective construction land marketization promoted rural industrial integration development? An empirical study based on county-level data in China - Zeng, Long; Zhang, Yilu; Yao, Jiazhou (Frontiers in Sustainable Food Systems, 2024)
The policy of rural collective construction land marketization (RCCLM) signifies that such land can currently be traded commercially. This not only breaks the government’s previous monopoly over the primary land market but also creates opportunities for revitalizing rural industries. This study uses county-level panel data from China between 2010 and 2022, treating the policy as a quasi-natural experiment. A multi-period difference-in-differences model is employed to examine its effects on rural industrial integration and the underlying mechanisms. The results indicate that, compared to non-pilot areas, the level of rural industrial integration in pilot areas has increased significantly by 1.47%. This finding remains robust after addressing potential model estimation biases caused by factors such as sample selection bias and reverse causality. Mechanism analysis indicates that RCCLM promotes rural industrial integration development by fostering county-level technological innovation and entrepreneurial activities. Further analysis shows that the policy exhibits significant effects in the eastern, western, and northeastern regions, as well as in counties with larger populations, while showing no significant effects in the central region and counties with smaller populations. Additionally, the RCCLM generates positive spatial spillovers on rural industrial integration of neighboring areas through resource sharing. This study provides valuable insights for research on RCCLM policy and rural industrial integration.